Knowledge, attitude and practice towards COVID-19 among pregnant women in a tertiary hospital in Pokhara, Nepal - Nepal, Benju; Nepal, Bibekti; Sharma, Bandana Gurung; Pandit, Chandika; Hachhethu, Rajju (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: The study was done to find out the knowledge, attitude, and practice of pregnant women towards COVID-19 in tertiary hospital of Pokhara, Nepal.Methods: A descriptive cross-sectional study was carried out among 385 pregnant women attending antenatal clinics of Gandaki Medical College starting from May 2021 to July 2021, by using self- administered questionnaire. The data was analyzed using statistical package for the social sciences version 21.0 and descriptive statistics were computed.Results: More than four‐fifths respondents were aware about COVID‐19. Half of them thought it transmits via human touch. One-fourth of them mentioned that delivery at the hospital during COVID-19 pandemic was unsafe. Almost half of them regretted conceiving, among which one quarter thought of aborting their fetus, half of them were against breastfeeding, and three-forth had regular antenatal care checkups. Majority of them took precautions to stay safe, where half of them responded that they would not breast fed baby if they got infected.Conclusions: Majority of the study population have good knowledge, attitude, and practice of COVID-19 disease. However, it is worrisome that some respondents thought of terminating her pregnancy, and some were unable to visit the hospital for routine antenatal care checkups and didn’t have proper knowledge about breastfeeding their child. Proper education must be given to the population to avert these negative attitudes while promoting a positive preventive attitude.